Dispersant for Reducing Mud Cakes of Slurry Shield Tunnel Boring Machine in Sticky Ground - Shisen Zhao; Shuchen Li; Zeen Wan; Manling Wang (Advances in Materials Science and Engineering)
When a slurry shield tunnel boring machine (TBM) encounters sticky ground during tunneling, mud cakes often occur on the cutter head due to the high stickiness of soil. The mud cakes caused several negative issues, such as high torque demand, advancement rate reduction, and additional costs. Existing studies have largely focused on Earth pressure balance TBMs; research on formation and mitigation measures of mud cakes in slurry shield TBMs is limited. Therefore, this study proposes the addition of dispersant to the slurry to prevent mud cakes during the tunneling of slurry shield TBMs by reducing stickiness of excavated clay. The basic properties of slurry were measured experimentally, and the effectiveness of dispersant in reducing the potential for mud cakes was investigated through mixing tests and viscosity experiments. A statistical analysis of the data was performed to determine relationships between slurry properties and material behaviors. The results showed that the slurry with dispersant had a lower viscosity and formed filter cakes more quickly, thereby meeting the performance requirements of a supporting fluid for slurry shield TBMs. Further, dispersant effectively reduced the empirical stickiness ratio and suspension viscosity. Therefore, a slurry with an appropriate dispersant content could effectively reduce the potential for mud cake formation.